Describing remote learning at Neutron Yogyakarta tutoring institution - Maretha, Dinda Genius Anggun; Mahmudah, Faisa Nirbita; Ahlam, Muhammad Naufal Husni; Putra, Rofiif Mahardhika; Nurnugroho, Burhanudin Arif (Universitas Ahmad Dahlan, 2021)
This study aims to describe the activities of remote learning at the tutoring institution (Lembimjar) Neutron Yogyakarta. This research was conducted at the head office of Lembimjar Neutron Yogyakarta using descriptive qualitative research methods. The subjects in the study were staff and teachers who were involved in remote learning. Data collection techniques through direct observation and unstructured interviews. The implementation of remote learning is carried out by collaborating with interactive live streaming learning through Zoom Meetings and programmatic consultation. Activities for remote learning as a form of adaptive learning during the COVID-19 pandemic.